2010
DOI: 10.18388/abp.2010_2398
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of oxidative stress in adjuvant arthritis. Comparison of efficacy of two pyridoindoles: stobadine dipalmitate and SMe1.2HCl.

Abstract: The aim of this study was to evaluate the therapeutic potential of oxidative stress (OS) reduction by using pyridoindole (PI) antioxidants in adjuvant arthritis (AA). The substances tested were stobadine dipalmitate (STB) and SMe1. AA was used as animal model. The experiments included healthy animals, control arthritic animals and arthritic animals with administration of PI in the oral daily dose of 15 mg/kg b.m during 28 experimental days. The rats were sacrificed on day 28. Clinical and biochemical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…TNF-α blockers may be used alternatively with other candidates for RA combination therapy. As resulted from our previous experiments (Bauerova et al ., 2005a ; 2005b ; 2008a ; 2008b ; 2009 ; Drábikova et al ., 2009 ; Dráfi et al ., 2010 ; Jančinova et al ., 2009 ; Kogan et al ., 2005 ; Mačičkova et al ., 2010 ; Poništ et al ., 2010 ; Sotnikova et al ., 2009 ; Štrosova et al ., 2008 ; 2009 ), all performed in the adjuvant arthritis model, substances with antioxidant properties have a high potency to be used in combination therapy with Mtx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-α blockers may be used alternatively with other candidates for RA combination therapy. As resulted from our previous experiments (Bauerova et al ., 2005a ; 2005b ; 2008a ; 2008b ; 2009 ; Drábikova et al ., 2009 ; Dráfi et al ., 2010 ; Jančinova et al ., 2009 ; Kogan et al ., 2005 ; Mačičkova et al ., 2010 ; Poništ et al ., 2010 ; Sotnikova et al ., 2009 ; Štrosova et al ., 2008 ; 2009 ), all performed in the adjuvant arthritis model, substances with antioxidant properties have a high potency to be used in combination therapy with Mtx.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the increased activity of GGT in AA is a result of elevated systemic oxidative stress. Stb was significantly effective in suppressing the increased activity of GGT in the joint, as expected from its antioxidant potential (Poništ et al ., 2010 ). The addition of Stb to Mtx caused significant improvement in lowering this biochemical parameter compared to Mtx monotherapy ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary studies (diet high in polyunsaturated fatty acids) in six female RA patients have reported significantly decreased neutrophil chemiluminescence . An animal study found significantly elevated whole blood chemiluminescence in adjuvant arthritis when compared with healthy control animals; which could be significantly reduced by antioxidants …”
Section: Introductionmentioning
confidence: 99%
“…To study the influence of neutrophils on pathogenesis of rheumatoid arthritis and to investigate the effects of new compounds on this process, different animal models of arthritis are used. One of them is the model of adjuvant arthritis induced by heat-inactivated Mycobacterium butyricum in Freund's adjuvant [13]. Mohr et al showed that under normal conditions, there were no neutrophils in the articular capsule of nonarthritic animals, while the inflamed synovial and capsular tissue of adjuvant injected animals is heavily infiltrated with neutrophils [7].…”
Section: Introductionmentioning
confidence: 99%